Inclusive sound and music serious games in a large‐scale responsive environment. (30th July 2018) - Mandanici, Marcella; Altieri, Federico; Rodà, Antonio; Canazza, Sergio
Abstract: In the last years, applications based on large‐scale responsive environments have risen up as a convincing aid for learning simple as well as complex concepts in a playful way. The full‐body interaction that characterizes these environments supports different learning styles and it is particularly fit for inclusion of participants with disabilities, due to its richness in emotional engagement and ease of use. This paper contains a short review of some serious games developed on a large‐scale responsive environment and devoted to music teaching and training of blind children. Authors present technology‐enhanced learning activities with the employment of three experimental applications: Harmonic Walk for teaching tonal harmony and melody harmonization; Jazz Improvisation for music re‐composition and score parts listening; and Following the Cuckoo Sound for helping blind children to walk straight. Quantitative and qualitative results report a great user engagement and a satisfying amount of successful records in formal task activities, which encourage further research to enhance education through large‐scale responsive environments applications and full‐body interaction. Moreover, the experience gained with blind children emphasizes the inclusive opportunities of these environments for the training and rehabilitation of disabled people.